Household Waste Management and Environmental Sanitation as Determinants of Infectious Disease Incidence in Urban Communities - Kusdiyah, Erny; Siregar, Mara Imam Taufiq; Hafizah, Hafizah; Gading, Patrick William; Perkasa, Tengku Arief Buana; aurora, Wahyu Indah Dewi; Darmawan, Armaidi (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Infectious diseases remain a public health problem in urban areas, particularly in densely populated settlements with poor environmental conditions. Inadequate household waste management and substandard sanitation can significantly increase the risk of disease transmission. This study aimed to analyze household waste management and environmental sanitation as determinants of infectious disease incidence among urban communities. A cross-sectional design was employed involving 120 households selected through stratified random sampling based on residential density levels. Data were collected using a structured questionnaire and an observation checklist to assess waste management practices, sanitation conditions, and the occurrence of infectious diseases within the past three months. Data were analyzed using Chi-square tests with a 5% significance level. The results showed that 56.7% of households had poor waste management practices, and 52.5% had inadequate sanitation. Infectious diseases were reported in 40% of households. There was a significant association between poor waste management and infectious disease incidence (p=0.01; OR=3.77; 95% CI=1.71–8.31), as well as between inadequate sanitation and disease occurrence (p=0.02; OR=3.29; 95% CI=1.52–7.09). This study concludes that environmental factors, particularly household waste management and sanitation conditions, play an important role in increasing the risk of infectious diseases in urban settings. Strengthening sanitation infrastructure, implementing community-based waste management, and enhancing public health education are essential strategies to prevent environmentally transmitted infections and promote healthier urban environments.